Environmental management and hotel profitability: operating performance matters - Alp Yenidogan; Tugba Gurcaylilar-Yenidogan; Nilufer Tetik (Tourism & Management Studies)
While there is growing consensus on the benefits of going green, the relative benefits of revenue-enhancing and cost-cutting effects of environmental practices over performance have remained a more conservative and less explored phenomenon in corporate management studies. The present study investigates the two parallel mediation effects of cost-saving and revenue generation on profitability through environmental management practices. A bootstrap method is employed to make a statistical inference of the causal mediation effects. The data collected from the lodging industry in Antalya/Turkey revealed that the revenue-enhancing and cost-cutting effects of environmental participation have a positive impact on profitability, while no difference was identified in the strength of the indirect effects. In conclusion, the findings of this study indicate a complementary effect of cost reduction and revenue enhancement for green profit.